Aurora A kinase phosphorylates serine 62 on Hec1 to affect mitotic kinetochore microtubule interactions - Sparrow, Sarah, author; DeLuca, Jennifer, advisor; Markus, Steven, committee member; Bailey, Susan, committee member (Colorado State University. Libraries, 2024)
The Hec1 protein plays an important role in ensuring successful chromosome segregation during cell division. Its 80 amino acid, unstructured, "tail" region is critical for kinetochore-microtubule attachment regulation, which is mediated through Aurora kinase phosphorylation. At least nine phosphorylation target sites within this domain have been identified, including the recently confirmed target site, serine 62 (S62). However, the functional significance of phosphorylation of this residue remains elusive. Here, we selectively target Aurora A and Aurora B kinase protein activities using the inhibitors MLN8054 and ZM447439, respectively, and study their effects on the dynamics of serine 62 phosphorylation in the Hec1 tail. Utilizing immunofluorescence, we demonstrated that inhibition of Aurora A kinase activity leads to a significant reduction in phosphorylation levels at serine 62. Additionally, using phospho-null mutants, we studied the effect of serine 62 phosphorylation on the creation of stable, tension-generating kinetochore-microtubule attachments by measuring the distance between sister kinetochores. Our findings reveal that alterations in serine 62 phosphorylation status result in subtle changes in interkinetochore distances showcasing the functional relevance of this phosphorylation event in regulating kinetochore-microtubule attachments. Furthermore, under conditions of nocodazole-induced mitotic arrest, we observe a marked decrease in phosphorylation at serine 62 suggesting a microtubule dependent regulation of this phosphorylation. These findings provide evidence supporting the role of Aurora A kinase in phosphorylating serine 62 of the Hec1 tail and shed light on the regulation of this critical post-translational modification during mitosis.
Keywords: mitosis